Study guides

☆☆

Q: What is r in this equation and how do you do it minus 5 equals 7 plus 3r?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Presumably this is a simultaneous equation in the form of: 3r-4s = 0 2r+5s = 23 Multiply all the terms in the top equation by 2 and in the bottom equation by 3: 6r-8s = 0 6r+15s = 69 Subtract the bottom equation from the top equation: -23s = -69 Divide both sides by -23 to find the value of s remembering that a minus number divided into a minus number is equal to a plus number: s = 3 Substitute the value of s into the original equations to find the value of r: Therefore: r = 4 and s = 3

5

3r-2 for r=65

It is (7 + a)r.

-5r + 8r + 5 = 3r +5

Related questions

(3r - 2)(3r - 2) or (3r - 2) squared.

(3r + 2)(r - 5)

If: -5 = 7+3r then the value of r works out as -4

Presumably this is a simultaneous equation in the form of: 3r-4s = 0 2r+5s = 23 Multiply all the terms in the top equation by 2 and in the bottom equation by 3: 6r-8s = 0 6r+15s = 69 Subtract the bottom equation from the top equation: -23s = -69 Divide both sides by -23 to find the value of s remembering that a minus number divided into a minus number is equal to a plus number: s = 3 Substitute the value of s into the original equations to find the value of r: Therefore: r = 4 and s = 3

3r + 3r + 2t = 6r + 2t

A math problem

9r = 3r + 6 subtract 3r from both sides 6r = 6 divide both sides by 6 r=1 ■

3r-r equals 12 = -9

17 = 13 - 3r Subtract 13 from bith sides: 4 = -3r Divide both sides by -3 : -4/3 = r or r = -1.3...

5

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

9r = 3r+6 Subtract 3r from both sides: 6r = 6 Divide both sides by 6 to find the value of r: r = 1

People also asked